E-Women in E-Business: Probing into State-led and Individual-based Finance-Gathering Initiatives of Filipinas during the Economic Pandemic Struggle - Catherine Hernando; Mymar Denise Nellas; Richelle Seares; Jan Brithney Navales; Rizza Sanchez (Journal of Social Science, 2022)
The paper seeks to investigate how the state, specifically the Department of Trade and Industry's Bayanihan COVID-19 Assistance to Restart Enterprises (CARES) program, responds to women's economic struggle and how Filipina entrepreneurs make use of the internet for ICT-based business as a solution for income-generating means and sales during the COVID-19 economic struggle. The research locale covers the experiences of online Filipina Entrepreneurs during this pandemic in the Philippines' Region VII, Central Visayas. The research is a qualitative and descriptive case study that uses a purposive sampling technique for data collection utilizing a researcher-made questionnaire and their experiences are analyzed using Colaizzi’s method. In our investigation, we found out that the pandemic has a detrimental effect on women’s businesses, from causing large losses in income and necessitating other sources of income to cover these losses. In solution, these women have entered into an online-operated business employing various marketing strategies to keep their businesses running. Fortunately, there is a consensus that entering in the online business has been a great economic opportunity and helped foster feelings of independence and financial freedom. However, despite this, challenges with internet connectivity in transacting with the government and customers have been a great obstacle and disadvantages such as; increased competition, the possibility of fraudulent transactions, and lack of transportation services experienced- all of which necessitate a systematic solution from the government. As a recommendation, the research's output is an innovative strategic governance framework integrating two vital aspects: Information and Communications Technology (ICT) and Gender and Development (GAD). Finally, the Philippines' new governance framework combines ICT-GAD to strengthen digital technologies and gender equality in addressing economic challenges. This breakthrough framework marries stale-led finance and individual-based gathering initiatives championed by one of the most vulnerable sectors in society — women. Keywords: E-women, E-business, E-commerce, entrepreneur, COVID-19 pandemic, digital entrepreneurship, state-led finance-gathering initiatives, individual-led finance-gathering initiatives